Pengembangan Perangkat Pembelajaran Matematika Model Kooperatif Tipe STAD dengan Media Powerpoint Ispring pada Materi Jajargenjang, Layang-Layang dan Trapesium di Kelas VII SMP - Endang Suprapti (MUST: Journal of Mathematics Education, Science and Technology, 2016)
The aim of this research are: to describe the process of development and instructional instruments of cooperative learning type STAD with Microsoft Power Point Ispring on topic parallelogram, the kite and trapezium at SMP Class Seven. The Subject of this research is SMP Muhammadiyah 13 Surabaya in class seven at year 2013-2014, tow parallel class are VII A an VII B. The model of development teaching material for this research is use 4-D Thiagarajan’s development instructional model. The development process consist of four phases, those are define, design, develop, and disseminate. Instructional instruments that developed are lesson plan, students work sheet, achievement test and the microsoft power point ispring media learning. The researches instrument are used validation’s instructional instruments sheet, observational sheet of student’s activities in learning, observational sheet of teacher ability to manage the instruction, and the quotioner of students responses. The instructional instruments that has been developed by the next one will be seen whether already as instructional instruments that was good that is an equipment that could support learning process so as the aim that it was hoped could be reached and be equipment pembelajaran that was developed in accordance with the development procedure of instructional instruments and met (1) Valid that is has divalidasi by the expert and filled the minimal criterion valid. (2) was tested, by filling the criterion: (a) the teacher's capacity managed pembelajaran was classified as effective (b) the Activity of the student was classified as active (c) the positive Criterion for the student's response to pembelajaran and the completeness of studying results in a classical manner was reached (d) the results Test studied met valid, reliable and sensitive. Based on the analysis in the development stage, was received by the conclusion that instructional instruments cooperative model mathematics the STAD type with the media Microsoft PowerPoint Ispring learning to material parallelogram, the kite and the trapezium in the SMP Muhammadiyah 13 VII classes filled the good criterion was based on results of the validation of the expert and results of the test that filled conditions that were determined that is, (1) the activity of the student during pembelajaran effective; (2) the teacher's capacity in managed learning process effective; (3) the student's response to pembelajaran active and the completeness of studying results in a classical manner was reached; and (4) the results test studied that was used sensitive, valid, and reliabel.